Current research in rabbit biotechnology - XYLOURI (Ε. ΞΥΛΟΥΡΗ) E. (Journal of the Hellenic Veterinary Medical Society, 2017)
The advance of biotechnology has created new methods in breeding farm animals. The purpose of the present study is the description and evaluation of the new technological techniques that are applied to rabbits. Following the contribution of rabbit to the scientific research, there is a detailed description of embryo transfer in rabbits. Several experimental studies are presented in order to compare the different methods that can be used. There is a brief description of in vitro fertilization in rabbits, a technique that can be combined with embryo transfer. The production of transgenic animals includes embryo transfer. This is the reason why each step of it it is described separately, while studies referring to transgenic rabbits are presented.